2015
DOI: 10.1039/c5ra07655b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and reduction performance of 1,1,1-trichloroethane in aqueous solution by means of a combination of persulfate and zero-valent iron

Abstract: 16In this study, the degradation performance of 1,1,1-trichloroethane (TCA) involving both 17 oxidation and reduction processes was investigated with an application of the persulfate-ZVI 18 (zero-valent iron) system, in which it is generally believed that SO4 −• -induced oxidation was 19 responsible for pollutants removal. The study was conducted with persulfate and 20 un-pretreated ZVI through batch experiments. The results showed that TCA was stable in the 21 presence of ZVI alone within 12 h and degraded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…•and • OH for efficient oxidation of arsenic(III) in water, while Gu et al [14] reported that efficient removal of 1,1,1-trichloroethane can be achieved using a similar system. For the PMS system, Ghanbari et al [15] reported that the ZVI/PMS system can be used to efficiently decolorize textile wastewater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…•and • OH for efficient oxidation of arsenic(III) in water, while Gu et al [14] reported that efficient removal of 1,1,1-trichloroethane can be achieved using a similar system. For the PMS system, Ghanbari et al [15] reported that the ZVI/PMS system can be used to efficiently decolorize textile wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ZVI has been employed to activate both PMS and PDS to generate ROS for pollutant removal. For instance, Hussain et al [ 13 ] reported that the ZVI/PDS system can be used to generate SO 4 •– and • OH for efficient oxidation of arsenic(III) in water, while Gu et al [ 14 ] reported that efficient removal of 1,1,1-trichloroethane can be achieved using a similar system. For the PMS system, Ghanbari et al [ 15 ] reported that the ZVI/PMS system can be used to efficiently decolorize textile wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various activation methods, zero-valent iron (ZVI) activation of PS has appeared to be a promising method. [14][15][16] ZVI activation is a cost-effective, efficient and environmentally friendly technology. 14,17 Additionally, ZVI not only serves as a slow-releasing source of dissolved Fe 2+ , but also avoids adding other anions that can lead to scavenging of SO 4 À c and possibly reducing the oxidation efficiency.…”
Section: Introductionmentioning
confidence: 99%